An Update of the Appropriate Treatment Strategies in Anaplastic Thyroid Cancer: A Population-Based Study of 735 Patients - Nai-si Huang; Xiao Shi; Bo-wen Lei; Wen-jun Wei; Zhong-wu Lu; Peng-cheng Yu; Yu Wang; Qing-hai Ji; Yu-long Wang (International Journal of Endocrinology)
Background. Anaplastic thyroid cancer (ATC) responds poorly to conventional therapies and requires a multidisciplinary approach to manage. The aim of the current study is to explore whether aggressive treatment is beneficial, especially the appropriate extent of surgery in ATC. Methods. Patients diagnosed with ATC from 2004 to 2014 were identified from the Surveillance, Epidemiology, and End Results (SEER) database and included in our study. Results. A total of 735 ATC patients were identified. The two-year overall survival (OS) rates for stage IVA, IVB, and IVC patients were 36.5%, 15.6%, and 1.4%, respectively. By directly comparing eight treatment modalities, we found that surgery+radiotherapy RT±chemotherapy was the most effective treatment strategy. surgery+chemotherapy and RT+chemotherapy had comparable results (hazard ratio HR=1.461, 95% confidential interval (CI): 0.843-2.531, P=0.177). Multivariate Cox regression analysis also showed increased mortality risk in patients with increased age (HR=1.022, P<0.001), tumor extension to adjacent structures (HR=1.649, P=0.013), and distant metastasis (HR=2.041, P<0.001), while surgery+RT (HR=0.600, P=0.004) and chemotherapy (HR=0.692, P=0.010) were independently associated with improved OS. Further analysis revealed that patients undergoing total/near-total thyroidectomy (TT) had superior OS to those receiving less than TT (P<0.001). In subgroup analysis, the benefit of TT remained significant in patients with tumors larger than 4.0 cm (HR=0.776, 95% CI: 0.469-0.887, P=0.007), with adjacent structure extension (HR=0.642, 95% CI: 0.472-0.877, P=0.005), including trachea and major vessels, but not in patients with early phase local disease such as tumor≤4.0 cm or tumor within the thyroid or with minimal extrathyroidal extension. Patients with very locally advanced disease or distant metastasis could not benefit from TT as well. Conclusions. In operable cases, surgery+RT±chemotherapy was the optimal treatment modality. Otherwise, RT+chemotherapy was the appropriate strategy. However, TT was not beneficial for very early stage or metastatic ATC.